A Seawater‐Corrosion‐Resistant and Isotropic Zero Thermal Expansion (Zr, Ta)(Fe, Co)2 Alloy. Issue 34 (20th July 2022) - Li, Wenjie; Lin, Kun; Yan, Yu; Yu, Chengyi; Cao, Yili; Chen, Xin; Wang, Chin‐Wei; Kato, Kenichi; Chen, Yan; An, Ke; Zhang, Qinghua; Gu, Lin; et al.
Abstract: Zero thermal expansion (ZTE) alloys as dimensionally stable materials are usually challenged by harsh environmental erosion, since ZTE and corrosion resistance are generally mutually exclusive. Here, a high‐performance alloy, Zr0.8 Ta0.2 Fe1.7 Co0.3, is reported, that shows isotropic ZTE behavior (αl = 0.21(2) × 10 −6 K −1 ) in a wide temperature range of 5–360 K, high corrosion resistance in a seawater‐like solution compared with classic Invar and stainless Invar, and excellent cyclic thermal and structural stabilities. Such stabilities are attributed to the cubic symmetry, the controllable magnetic order, and the spontaneously formed passive film with Ta and Zr chemical modifications. The results are evidenced by X‐ray/neutron diffraction, microscopy, spectroscopy, and electrochemistry investigations. Such multiple stabilities have the potential to broaden the robust applications of ZTE alloys, especially in marine services. Abstract : Nowadays, zero thermal expansion (ZTE) alloys are challenged by other environmental instabilities beyond the dimensional stability. Here, a ZTE alloy, Zr0.8 Ta0.2 Fe1.7 Co0.3, is studied, which shows multiple stabilities, including dimensional stability (ZTE, αl = 0.21(±2) × 10 −6 K −1 from 5 to 360 K), shape stability (isotropic), cycling stability, and environmental stability.